Design of Elastomeric Bridge Bearing Pad Compound Formula Based on Hydrogenated Natural Rubber - Santi Puspitasari; Adi Cifriadi (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Laminated elastomeric bearing pad which is commonly produced by natural or chloroprene rubber is functioned as isolation system in bridge or flyover structures. In the research, hydrogenated natural rubber (HNR) was evaluated its feasibility to be used as base elastomer on steel-laminated bearing pad production by designing rubber compound formula. The compounding procedures of HNR applied various vulcanization system and carbon black filler types. The physical and mechanical tests result showed that only hardness parameter could fill the standar quality requirement of commercial elastomeric bearing pad as stated in AASHTO M251 in the range of 50